Analysis of Mathematical Problem Solving Ability for Tenth Grader of SMK Boarding School in Terms of Learning Styles - Rahayu, Dwi Purnaning; Supriyono, Supriyono; Waluya, St. Budi (Department of Mathematics, Universitas Negeri Semarang, 2017)
The purpose of this research was to describe mathematics problem solving skills of SMK Class X boarding school students which in terms of learning styles by using Anchored Instruction models based neuroscience. This is a qualitative research. The subjects of this research are 9 students of SMK N Jawa Tengah, were classified into 3 to the learning styles that is visual, auditory, and kinesthetic.The methods of collecting data in this research using a questionnaire of learning style, mathematics problem solving test, and interview. Analysis of mathematics problem Âsolving skills refer to the stage of the Polya problem solving. The results of this research showed that: 1) students 'visual and auditory with the same number are most numerous in the class X SMK N Jawa Tengah, it points out that the habits of the three subjects in accordance with the characteristics of learning styles such as when learning to learn math students visual prefer to read a book with pictures or tables, students auditory prefers to listen to the explanation of the teacher, while students kinesthetic rather try or practice directly through exercises; 2) in general, students' visual, auditory, and kinesthetic at high group, medium group, and low group able to solve the problem through the stages of understanding the problem, devising a plan, carrying out the plan, and looking back.